Analysis of genetic sandbodies and coal seams with coal-bearing of Middle-Lower Jurassic in the Junggar Basin - Zongquan, Yao; Wei, Wang; Yong, Wang; Zongrui, Xie; Xingtao, Yang; Fan, Yang; Qihao, Zhou (Frontiers in Earth Science, 2024)
IntroductionThe sediment genetic mechanisms have always been an important branch of the “source-sink” system, and it is also a research hotspot.MethodsConglomerate, sandstone, and coal are developed of Middle-Lower Jurassic in the Junggar Basin, and the genetic mechanism is not clear, which restricts further exploration of oilfield. Based on the core carefully, test data, and outcrop sections, Badaowan and Xishanyao formations are analyzed.ResultsFive types of conglomerate lithofacies and sandstone lithofacies, two kinds of mudstone lithofacies, and one type of coal are identified. Based on the structural-genetic mechanism, the debris flow and traction current with conglomerate are developed, and a method of the semi-quantitative identifying index is proposed based on the sedimentary sequence of lithological characteristics, MPS/BTh, and grain size characteristics as the identification criteria. Depending on fluvio-delta, the genetic bodies of the distribution channel, subaqueous distribution channel, mouth bar, braided channel, and overbank sandstone are divided.DiscussionBy integrating structural, paleoclimatic, and sedimentary environment, it was observed that coal in the Badaowan Formation has the characteristics of continuous and stable distribution of thick layers, whereas multiple sets of discontinuous and instable distribution are observed in the in Xishanyao Formation. Finally, the filling model is established, and the superposition and distribution of sandbodies are clarified.